The Effectiveness of Emotion Focused Therapy and Digital Detox on Fear of Missing Out in Social Media Among Adolescents: A Mixed Method Study - Muhammad Reyhan Fadhlur Rahman; Muhammad Akbar Suryana; Muthiara Putri Nurroby; Nindia Ismi Hidayah; Maria Yulianti (Indonesian Journal of Global Health Research, 2025)
FoMO can cause emotional distress that impacts mental health due to inadequacy compared to others. One complementary therapy to overcome fear of missing out among adolescents is emotion-focused therapy and digital detox. The purpose of this research is to determine the effect of emotion-focused therapy and digital detox on fear of missing out on social media among adolescents. This study used a mixed-methods exploratory sequential design and was conducted at SMAN 4 Sukabumi City. Qualitative participants were 14 students from school representatives using purposive sampling. Quantitative respondents were 60 students divided into two groups using stratified random sampling. The instruments used were an interview guide and a FoMO scale questionnaire, which were declared valid and reliable. Statistical analysis used paired and independent sample t-tests and repeated measures ANOVA. There was a significant effect of the combination of Sundanese-language emotion-focused therapy and digital detox on fear of missing out in adolescents over time in the intervention group (p < 0.001, d = 0.436). It was concluded that the combination of emotion-focused therapy and digital detox was very effective in reducing FoMO levels. Further research is expected to be conducted with a larger sample size to obtain more credible results.